2010
DOI: 10.1002/hbm.21156
|View full text |Cite
|
Sign up to set email alerts
|

Clinical functional MRI of the language domain in children with epilepsy

Abstract: Functional MRI (fMRI) for the assessment of language functions is increasingly used in the diagnostic workup of patients with epilepsy. Termed "clinical fMRI," such an approach is also feasible in children who may display specific patterns of language reorganization. This study was aimed at assessing language reorganization in pediatric epilepsy patients, using fMRI. We studied 26 pediatric epilepsy patients (median age, 13.05 years; range, 5.6-18.7 years) and 23 healthy control children (median age, 9.37 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…This means that an atypical value of LI (LI<0.1) reflects a greater contribution from the right hemisphere region. Recent studies (Staudt et al, 2001; Thiel et al, 2005), including several by our group (Tillema et al, 2008; Wilke et al, 2011; Yuan et al, 2006) have demonstrated right-hemispheric involvement in typically left-lateralizing language production tasks in pathological conditions such as stroke or epilepsy but the efficacy of such a non-dominant switch has been questioned (Anderson et al, 2011; Saur et al, 2010; Winhuisen et al, 2007). Therefore, we believe that atypical language representation in subjects with normal language skills (data points in Figure 2 represented by the triangles in the range of LI<0.1) and no history of underlying neurological condition (e.g., epilepsy, stroke or trauma) is genetically mediated as suggested by the recent discoveries of correlations between certain genes and handedness.…”
Section: Discussionmentioning
confidence: 99%
“…This means that an atypical value of LI (LI<0.1) reflects a greater contribution from the right hemisphere region. Recent studies (Staudt et al, 2001; Thiel et al, 2005), including several by our group (Tillema et al, 2008; Wilke et al, 2011; Yuan et al, 2006) have demonstrated right-hemispheric involvement in typically left-lateralizing language production tasks in pathological conditions such as stroke or epilepsy but the efficacy of such a non-dominant switch has been questioned (Anderson et al, 2011; Saur et al, 2010; Winhuisen et al, 2007). Therefore, we believe that atypical language representation in subjects with normal language skills (data points in Figure 2 represented by the triangles in the range of LI<0.1) and no history of underlying neurological condition (e.g., epilepsy, stroke or trauma) is genetically mediated as suggested by the recent discoveries of correlations between certain genes and handedness.…”
Section: Discussionmentioning
confidence: 99%
“…33 Atypical language representation may also occur in patients with normal structural MR imaging, mesial temporal sclerosis, focal cortical lesions, and stroke. 39,40 Language lateralization deduced from fMRI concurs with the Wada test in 80% to 90% of patients when using conjunction analysis of 3 language paradigms or semantic decision paradigm, suggesting the clinical usefulness of the test. 7,9,41,42 Concordance between fMRI and Wada test is the highest for patients with right TLE with left language dominance and for frontal language areas; and the lowest for patients with left TLE with left language dominance.…”
Section: Localization Of Language Networkmentioning
confidence: 89%
“…68 Effect of epileptic activity and antiepileptic drugs Antiepileptic drugs can affect cognitive processing. 40 Topiramate has an effect on activation in the basal ganglia, anterior cingulated, and posterior visual cortex and can cause reduced deactivation of the default mode network-related areas during a language task, suggesting interference in cognitive processing. 69,70 There has also been some evidence suggesting that atypical language reorganization/dominance may be affected by the presence and absence of ongoing epileptic activity.…”
Section: Postoperative Findingsmentioning
confidence: 99%
“…Moreover, there are clear limitations to the use of invasive methods – the Wada test or electrocorticography — as “gold standards”, like fMRI, may be flawed and under various circumstances yield faulty information [Gaillard et al, 2011]. Finally, recent clinical practice [De Ribaupierre et al, 2012; Szaflarski et al, 2012; Wilke et al, 2011] in most pediatric epilepsy centers, especially for younger patients, has de-emphasized the Wada test. As the standard is not established we present data for commonly used methods and report our observations on their concordance, not their “correctness.” Further, we have made some observations about when and how partial discordance arises.…”
Section: Discussionmentioning
confidence: 99%